Here's the pitch : the dilemma of selecting a new outdoor playing field for Sunshine State University - Simmons, Jason; Popp, Nels; Greenhalgh, Greg (London : Human Kinetics, Inc., 2015)
The outdoor athletic fields of Sunshine State University are in poor condition. Overuse, insufficient drainage, and a lack of human and financial resources have contributed to the fields' deterioration. Sunshine State University's director of athletics, Emily Rodriguez, has decided to replace the existing fields, but that decision is just the tip of the iceberg. Rodriguez now must decide on a natural or synthetic surface for the new fields. This decision is complex because cost, maintenance, durability, player safety, and player preference must all be considered. Both surfaces have their advantages and disadvantages. In the end, Rodriguez must decide which surface is right for Sunshine State University.
Originally published in Simmons, J., Popp, N., & Greenhalgh, G. (2015). Here's the pitch: The dilemma of selecting a new outdoor playing field for Sunshine State university. Case Studies in Sport Management, 4(12), 54-61. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Rodriguez, Emily; Sunshine State University; Universities and colleges -- Finance; Universities and colleges -- Management; Athletic fields